Some notes on the historical roots of contemporary interpersonal relationships in the christian Philippines.[article]. - Morais, Robert J.
A brief look into the literature on the Filipino's ritual kinship, utang na loob, and patron/client bounds reveals that each of these patterns of interpersonal relationship shows consistency in character as each has expressed itself from the pre-Hispanic period to the present. It is suggested that such patterns had been in existence among the uncolonized Filipinos. The Spanish rule, through its religious and economic influences, merely contributed to the formalization and intensification of what were already existing values and modes of interpersonal relationship. The author calls for more studies of this kind which explores the historical roots of other cultural parameters of Filipino experiences.